Stellar Collisions in Galactic Nuclei: Impact on Destructive Events Near a Supermassive Black Hole - Shmuel Balberg; Gilad Yassur (The Astrophysical Journal, 2023)
The centers of galaxies host both a supermassive black hole and a dense stellar cluster. Such an environment should lead to stellar collisions, possibly at very high velocities so that the total energy involved is of the same order as supernova explosions. We present a simplified numerical analysis of the destructive stellar collision rate in a cluster similar to that of the Milky Way. The analysis includes an effective average two-body relaxation Monte Carlo scheme and general relativistic effects, as used by Sari & Fargione, to which we added explicit tracking of local probabilities for stellar collisions. We also consider stars which are injected into the stellar cluster after being disrupted from a binary system by the supermassive black hole. Such stars are captured in the vicinity of the black hole and enhance the expected collision rate. In our results we examine the rate and energetic distribution function of high-velocity stellar collisions, and compare them self-consistently with the other destructive processes which occur in the galactic center, namely tidal disruptions and extreme mass ratio inspirals.